MiNNLO $$_{\text {PS}}$$ PS : optimizing $$2→ 1$$ 2 → 1 hadronic processes - Pier Francesco Monni; Emanuele Re; Marius Wiesemann (European Physical Journal C: Particles and Fields, 2020)
Abstract We consider the MiNNLO $$_PS$$ PS method to consistently combine next-to-next-to-leading order (NNLO) QCD calculations with parton-shower simulations. We identify the main sources of differences between MiNNLO $$_PS$$ PS and fixed-order NNLO predictions for inclusive observables due to corrections beyond NNLO accuracy and present simple prescriptions to either reduce or remove them. Refined predictions are presented for Higgs, charged- and neutral-current Drell Yan production. The agreement with fixed-order NNLO calculations is considerably improved for inclusive observables and scale uncertainties are reduced. The codes are released within the POWHEG-BOX.